Model Legislation of the Commonwealth of Independent States in the Fight against Terrorism Financing - S. V. Muradyan (Московский журнал международного права, 2011)
The article presents an analysis of the model legislation of the Commonwealth of Independent States in the sphere of fighting against terrorism financing. Suggestions on increase of its effectiveness are developed. This legislation has been tested for its adherence to international standards in combating terrorism and its financing. Particular attention is paid to harmonization of national legislation of CIS member-states in this area.The author comes to the conclusion that the system of fighting against the terrorism financing, developed by the CIS Inter-parliamentary assembly, is actual and effective, except for some gaps in the model legislation, mainly concerning determinations of concepts. The exit from the current situation is complicated by the lack of a unified approach of scientists and practical workers, regarding the definition of terrorism.